Gamification-Based Learning Through QuizWhizzer on Indonesian Students’ Grammar Achievement: Pembelajaran Berbasis Gamifikasi Melalui QuizWhizzer terhadap Prestasi Tata Bahasa Siswa Indonesia - Nur Haira; Resdilla Pratiwi; Zulfikar Zulfikar (Journal of Innovative and Creativity, 2025)
This study aims to examine whether the use of the QuizWhizzer application affects students' achievement in grammar and how significant the effect is. This study was conducted at SMA Negeri 1 Panyabungan Selatan using a quantitative method with an experimental design. Two classes were involved as samples: class X-1 consisting of 20 students as the experimental group taught using QuizWhizzer, and class X-2 consisting of 19 students as the control group taught using worksheets. Data were collected through tests, and then analyzed by applying normality tests, homogeneity tests, and independent sample t-tests. The results showed that students in the experimental class showed a significant improvement in their grammar achievement compared to those in the control class, who only showed slight progress. The t-test analysis revealed that t-count (2.639) was higher than t-table (2.026) and the significance value was 0.012 < 0.05. This indicates that QuizWhizzer has a significant positive effect on the grammar achievement of tenth-grade students of SMA Negeri 1 Panyabungan Selatan.